1997
DOI: 10.1007/s004110050063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lithium chloride as a potential radioprotective agent on radiation response of DNA synthesis in mouse germinal cells

Abstract: Mouse spermatogonial germ cells are highly sensitive to ionizing radiation. Lithium salts are reported to stimulate the postirradiation recovery of hematopoietic marrow cells. We have, therefore, examined whether administered lithium chloride (LiCl) would also be able to protect the mouse germinal cells against radiation injury. Taking DNA synthesis as an endpoint, our results show that the testicular DNA-specific activity in irradiated mice was higher by 61% on average when they had been pretreated with LiCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…To further validate that the increased size of the irradiated neurospheres after lithium treatment was due to increased numbers of proliferating cells, rather than hypertrophy, we assessed BrdU incorporation in NSPCs 48 hours after irradiation (Fig. 2C ), confirming that 3 mM LiCl recruits NSPCs into proliferation and restores the proliferative capacity halted after irradiation, as indicated by increased DNA synthesis also in vivo [ 30 , 63 ]. In support of this, the cell cycle distribution of NSPCs after irradiation revealed that the reduction of NSPCs in S phase could be rescued by 3 mM, but not 1 mM, LiCl treatment, with full restoration of proliferation as early as 6 hours after irradiation, and maintained protection at least up to 72 h after irradiation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To further validate that the increased size of the irradiated neurospheres after lithium treatment was due to increased numbers of proliferating cells, rather than hypertrophy, we assessed BrdU incorporation in NSPCs 48 hours after irradiation (Fig. 2C ), confirming that 3 mM LiCl recruits NSPCs into proliferation and restores the proliferative capacity halted after irradiation, as indicated by increased DNA synthesis also in vivo [ 30 , 63 ]. In support of this, the cell cycle distribution of NSPCs after irradiation revealed that the reduction of NSPCs in S phase could be rescued by 3 mM, but not 1 mM, LiCl treatment, with full restoration of proliferation as early as 6 hours after irradiation, and maintained protection at least up to 72 h after irradiation (Fig.…”
Section: Discussionmentioning
confidence: 99%